2017
DOI: 10.1177/0007650317696314
|View full text |Cite
|
Sign up to set email alerts
|

Business News Framing of Corporate Social Responsibility in the United States and the United Kingdom: Insights From the Implicit and Explicit CSR Framework

Abstract: This study aims to contribute to the understanding of business news coverage of corporate social responsibility (CSR) within a comparative international context by investigating two business newspapers, The Wall Street Journal from the United States and The Financial Times from the United Kingdom. Drawing on the news framing research and the implicit and explicit CSR framework of Matten and Moon, this content analysis shows that business news coverage of CSR in the United States and in the United Kingdom diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Likewise, another important theoretical contribution of the present study is that it adds to the existing literature on CSR from the perspective of a developing economy. The majority of past studies in this regard were conducted in developed countries [118,119]. The authors' argument here is that developed and developing economies are dissimilar and CSR studies conducted in developed countries cannot be generalized in the context of developing nations.…”
Section: Discussionmentioning
confidence: 89%
“…Likewise, another important theoretical contribution of the present study is that it adds to the existing literature on CSR from the perspective of a developing economy. The majority of past studies in this regard were conducted in developed countries [118,119]. The authors' argument here is that developed and developing economies are dissimilar and CSR studies conducted in developed countries cannot be generalized in the context of developing nations.…”
Section: Discussionmentioning
confidence: 89%
“…First, this examination focused on only one country. Although Switzerland certainly delivers a meaningful case due to its globally oriented economy, the perception of CSR by stakeholders (Chapple & Moon, 2005;Golob & Bartlett, 2007) as well as media coverage of CSR (T. H. Lee & Riffe, 2017) have been shown to depend on the country under review. Further research could therefore look at the effects of news media coverage and social media communication related to CSR in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Lee & Carroll, 2011;Luo et al, 2011;Vogler & Gisler, 2016). T. H. Lee and Riffe (2017) found a positive tone toward referenced corporations in relation to CSR in coverage of The Wall Street Journal and The Financial Times. In their study, they also showed that the U.K.-based Financial Times exhibited a significantly higher ratio of positive tone toward the referenced corporations than its U.S.-based counterpart.…”
Section: Csr and Corporate Reputationmentioning
confidence: 99%
“…It must be admitted that, on the one hand, there are differences in the perception and implementation of CSR practices related to different cultures [37][38][39][40][41][42][43] or corporate culture (e.g., [44]). One of the important conditions for understanding the role in the context of social responsibility is related to the perception of shareholders and the competencies of hired professionals to develop the strategies and use ethical potential.…”
Section: Literature Reviewmentioning
confidence: 99%